SHM_97645_HST_3D Stone Boat Axe (Type C:2) - National Historical Museums (National Historical Museums, 2026)
Structured light 3D model of a stone boat axe (type C:2) from the Swedish Middle Neolithic, collected in the field from Bäne in Västra Götaland and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=398

Link to Sök I Samlingarna

https://samlingar.shm.se/object/D1E9B206-488F-494D-8EFD-3EF29D142947
Keywords: Archaeology; Archaeology; Archaeology/history; Structured Light Scanning; 3D Model; Museum Object; Dynamic Collections; Bäne; Swedish Middle Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi